2003
DOI: 10.1161/01.str.0000056169.45365.15
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of SolCD39, a Novel Platelet Aggregation Inhibitor, on Transient Middle Cerebral Artery Occlusion in Rats

Abstract: Background and Purpose-SolCD39 is a soluble form of recombinant human ecto-ATP/ADPase (NTPDase1) and represents a new class of antithrombotic agents. SolCD39 blocks and reverses platelet activation, preventing recruitment of additional platelets into a growing thrombus. The purpose of this study was to examine the effect of solCD39 on neurological deficit, infarct size, and extent of edema after transient middle cerebral artery occlusion (MCAO) in rats. Methods-Physiologically controlled Sprague-Dawley rats un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…To compensate for the effect of brain edema, corrected infarct volumes were calculated as previously described using: Corrected infarct areaϭMeasured infarct areaϫ{1Ϫ[(Ipsilateral hemisphere areaϪContralateral hemisphere area)/Contralateral hemisphere]}. 12 Infarct volumes were expressed as percentages of total hemispheric volumes.…”
Section: Infarct Volume Measurementmentioning
confidence: 99%
“…To compensate for the effect of brain edema, corrected infarct volumes were calculated as previously described using: Corrected infarct areaϭMeasured infarct areaϫ{1Ϫ[(Ipsilateral hemisphere areaϪContralateral hemisphere area)/Contralateral hemisphere]}. 12 Infarct volumes were expressed as percentages of total hemispheric volumes.…”
Section: Infarct Volume Measurementmentioning
confidence: 99%
“…Animal studies have shown that a new soluble form of the extracellular region of CD39 (solCD39) has systemic antithrombotic effects 30,31 ; however, antiplatelet therapy also tends to induce systemic bleeding. 2 This is an important limitation to clinical applicability and indicates a potential advantage of local gene transfer into injured vessels.…”
Section: Furukoji Et Al Placental E-ntpdase Suppresses Thrombosismentioning
confidence: 99%
“…Belayev et al [28] also reported that a soluble form of CD39/NTPDase1 nucleotidase utilized in a rat model of middle cerebral artery occlusion was capable of significantly reducing total infarct areas at various coronal levels when administered, both before ischemia and after 3 hours of recirculation. Thus, soluble nucleotidase enzymes appear to be very attractive candidates for therapeutic use in thrombotic pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…One of these enzymes, NTPDase1 (also known as CD39 [25][26][27]) is present in vascular endothelial cells and functions in maintaining hemostasis. The therapeutic utility of a soluble form of CD39/NTPDase1 apyrase has been demonstrated in a variety of cardio-and cerebrovascular disorders, including middle cerebral artery occlusion [1,28], intestinal ischemia-reperfusion injury [29], and arterial balloon injury [30,31]. The NTPDase1 enzyme acts via the same mechanism as the SCAN enzymes used in the present study -inhibition of platelet aggregation and clotting by hydrolysis of the platelet aggregation agonist, ADP, thereby preventing activation of the platelet purinergic receptors, which normally lead to platelet activation, shape change, aggregation, and clotting.…”
Section: Discussionmentioning
confidence: 99%